SPE–UPLC–MS/MS method for sensitive and rapid determination of aripiprazole in human plasma to support a bioequivalence study - Patel, Daxesh P.; Sharma, Primal; Sanyal, Mallika; Shrivastav, Pranav S. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2013)
► An improved UPLC–MS/MS method for determination of aripiprazole in human plasma. ► Highly sensitive and rapid compared to all existing methods in biological matrices. ► Practically free from endogenous matrix interference. ► Successful bioequivalence study in healthy Indian subjects. ► Reproducibility of study data is demonstrated by incurred sample reanalysis. An improved and rugged UPLC–MS/MS method has been developed and validated for sensitive and rapid determination of aripiprazole in human plasma using aripiprazole-d8 as the internal standard (IS). The analyte and IS were extracted from 100μL of human plasma by solid-phase extraction using Phenomenex Strata-X (30mg, 1cc) cartridges. Chromatography was achieved on an Acquity UPLC BEH C18 (50mm×2.1mm, 1.7μm) analytical column using methanol: 10mM ammonium formate (85:15, v/v) as the mobile phase with isocratic elution. Quantitation was done using multiple reaction monitoring in the positive ionization mode. The linearity of the method was established in the concentration range 0.05–80ng/mL. The mean extraction recovery was greater than 96% across QC levels, while intra- and inter batch accuracy and precision (% CV) values ranged from 97.4 to 101.9% and from 1.20 to 3.72% respectively. The relative matrix effect in eight different lots of plasma samples, expressed as % CV for the calculated slopes of calibration curves was 1.08%. The stability of aripiprazole was studied under different storage conditions. The validated method was used to support a bioequivalence study of 10mg aripiprazole formulation in 36 healthy Indian subjects.